Exploring luxury fashion brands' strategic response to crisis: a multiple case study on surviving the Global Financial Crisis - Worrell, Jennifer H., author; Miller, Nancy J., advisor; Diddi, Sonali, advisor; DeTienne, Dawn, committee member; Engel-Enright, Carol, committee member (Colorado State University. Libraries, 2018)
The Global Financial Crisis, 2007-2010, affected the luxury industry, causing an 8% overall decline, major consumer behavior shifts, and increased competitive pressure on luxury fashion brands' strategic responses (Cavender & Kincade, 2014; Halliburton & Kellner, 2011; Savelli, 2012; Som & Blanckaert, 2015). The few studies conducted on luxury brands' strategic response to the financial crisis (Cavender & Kincade, 2014; Som & Blanckaert, 2015) have focused on luxury conglomerates, e.g. parent companies owning multiple individual brands (Som & Blanckaert, 2015) and mono-brand houses, e.g. individual brands that design, manufacture, and distribute goods directly to the consumer, through multi-brand retailers, and/or other channels like licensed boutiques (Brun, Caniato, Caridi, Castelli, Miragliotta, Ronchi, Sianesi, & Spina, 2008). However, the multi-brand retailer is a key collaborator for conglomerates and mono-brands alike as they distribute mono-brand houses' goods in their own unique, luxury retail environment (Brun et al., 2008; Iannilli, 2014). Despite their important role in the luxury business landscape, the multi-brand retailer has not been considered in the literature. Therefore, this exploratory multiple case study sought to redress this gap through the investigation of the brand management strategies chosen by luxury fashion executives from a multi-brand retailer and a mono-brand house during the Global Financial Crisis. Semi-structured interviews were conducted with senior executives from two case companies, along with senior executives from a small set of auxiliary luxury brands for triangulation. The findings from this qualitative study offer practical insight on luxury brand management during crisis conditions, as well as the advancement of academic knowledge through the examination of a re-conceptualized luxury brand management framework based on the luxury brand management models previously put forth by Cavender and Kincade (2015) and Som and Blanckaert (2015).
Keywords: crisis; mono-brand; retail; luxury; brand management; multi-brand